THE QUESTION OF THE DECLINE OF TRZCINIEC CULTURE IN WESTERN MAŁOPOLSKA. TRZCINIEC CULTURE VS. LUSATIAN CULTURE - Górski, Jacek (Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Prahistorii, Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Wschodni, 1998)
The Trzciniec Culture, Trzciniec Cultural Circle and Trzciniec Horizon are the names of a cultural area in the borderland of Western and Eastern Europe at the 2nd millenium BC. For over half a century a discussion has been going on over the taxonomic identification (chronological and spatial) and genetic and ethnic interpretation of this cultural unit. In the debate, the 1980's and 1990's mark a significant cognitive turn caused by the growth of the corpus of sources, the use of systematic methods for the study of mobile sources and the proliferation of regional 14C datings. The present volume of "Baltic-Pontic Studies" is an attempt to register this breakthrough and a proposal for a new fitting of the Trzciniec phenomenon into the synthesis of Early Bronze Age Europe. The records include rudiments of new regional systematizations, foundations of their chronologies based on radiocarbon datings and a discussion of the mechanisms of socio-cultural changes which gave rise to the Trzciniec cultural area and later contributed to its disintegration. A long-term intention of this volume giving a multifaceted view of the effects of the said cognitive breakthrough is to encourage a careful scrutiny of the development mechanisms of the European Early Bronze Age Civilization, in particular the role played in them by the societies inhabiting the drainages of the Baltic and Pontic Seas.